Understanding soot particle size evolution in laminar ethylene/air diffusion flames using novel soot coalescence models. Issue 4 (3rd July 2016) - Veshkini, Armin; Dworkin, Seth B.; Thomson, Murray J.
Abstract : Two coalescence models based on different merging mechanisms are introduced. The effects of the soot coalescence process on soot particle diameter predictions are studied using a detailed sectional aerosol dynamic model. The models are applied to a laminar ethylene/air diffusion flame, and comparisons are made with experimental data to validate the models. The implementation of coalescence models significantly improves the agreement of prediction of particle diameters with the experimental data. Sensitivity of the soot prediction to the coalescence parameters is analysed. Finally, an update to the coalescence model based on experimental observations of soot particles in the flame oxidation regions has been introduced to improve its predicting capabilities.